2006
DOI: 10.1007/s00284-005-0402-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Genetic Transformation System for the Ochratoxigenic Fungus Aspergillus carbonarius

Abstract: Aspergillus carbonarius is a potent ochratoxin A producer that has been found in products such as grapes, coffee, spices, and cocoa. Ochratoxin A has nephrotoxic effect, and it has been classified as a possible carcinogenic substance for humans. Here we describe for the first time a transformation system for A. carbonarius, providing an important step towards its genetic manipulation. Conidia were transformed to acquire hygromycin B resistance using the AGL-1 strain of Agrobacterium tumefaciens. Genetic transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 21 publications
1
2
0
5
Order By: Relevance
“…In the case of F. avenaceum pre-induction of the used A. tumefaciens strain, for 16 hours, did not result in a statistically significant higher number of colonies (Figure 6). Similar results have been reported for Aspergillus carbonarius [41] and Magnaporthe grisea [42]. Mullins and co-workers found that pre-induction was not essential for the success of ATMT in the case of Fusarium oxysporum, but that the transformation process was delayed compared to experiments including pre-induction [43].…”
Section: Resultssupporting
confidence: 81%
“…In the case of F. avenaceum pre-induction of the used A. tumefaciens strain, for 16 hours, did not result in a statistically significant higher number of colonies (Figure 6). Similar results have been reported for Aspergillus carbonarius [41] and Magnaporthe grisea [42]. Mullins and co-workers found that pre-induction was not essential for the success of ATMT in the case of Fusarium oxysporum, but that the transformation process was delayed compared to experiments including pre-induction [43].…”
Section: Resultssupporting
confidence: 81%
“…Este nível de sensibilidade foi similarmente observado para outras espécies de Aspergillus (PUNT et al, 1987) e já havia sido relatada para a linhagem ITAL 99 de A. carbonarius por Morioka et al (2006) Dentre os 238 transformantes analisados em meio agar-coco para a produção de ocratoxina A, nove (3,7%) possíveis mutantes com redução da produção desta toxina foram identificados baseado na redução e/ou ausência de fluorescência azul esverdeada na colônia sob luz ultravioleta. Por outro lado, dois (0,8%) supostos mutantes com aumento na produção desta toxina também foram identificados.…”
Section: Resultsunclassified
“…A transformação genética da linhagem ITAL 187 foi realizada como descrito por Morioka et al (2006) com algumas modificações. Rapidamente, após cinco dias de crescimento da linhagem ITAL 187 em MC a 28ºC, foi preparada uma suspensão contendo 1x10 6 conídios/mL de meio de indução.…”
Section: Transformação Genética Mediada Por a Tumefaciensunclassified
“…The ATMT via germinated conidia could avoid the preparation of protoplast, which is usually expensive and timeconsuming (Song et al, 2004). Random integration of a single copy into the fungal genome is another important character for functional genomic study (Morioka et al, 2006). In this study, the hph was demonstrated to be randomly integrated in P. digitatum genome with single copy by Southern blot and sequencing of 14 randomly selected transformants.…”
Section: Analysis Of Fungal Transformantsmentioning
confidence: 91%